2005
DOI: 10.1111/j.1570-7458.2005.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Does mother really know best? Oviposition preference reduces reproductive performance in the generalist parasitoid Aphidius ervi

Abstract: The reproductive success of female parasitoids is dependent on their ability to accurately assess the suitability of a host for larval development. For generalist parasitoids, which utilize a broad range of species and instars as hosts, a set of assessment criteria determines whether a host is accepted or rejected. The suitability of a host, however, can only be imperfectly assessed by the female parasitoid, which can result in the selection of lesser quality hosts for oviposition. In this study we explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 48 publications
1
71
1
5
Order By: Relevance
“…In no-choice assays, B. communis did not refrain from attacking larger or older aphid stages or aphids that exhibited stronger defenses. This could reflect either a low response threshold of B. communis for oviposition (Mackauer et al, 1996) or acceptance decisions resulting from its lack of previous experience (Henry et al, 2005). Binodoxys communis females encountered and probed larger aphid stages at a lower frequency and with many probing attempts unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In no-choice assays, B. communis did not refrain from attacking larger or older aphid stages or aphids that exhibited stronger defenses. This could reflect either a low response threshold of B. communis for oviposition (Mackauer et al, 1996) or acceptance decisions resulting from its lack of previous experience (Henry et al, 2005). Binodoxys communis females encountered and probed larger aphid stages at a lower frequency and with many probing attempts unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Various relationships exist between parasitoid development time and host age at oviposition (Hopper, 1986;Colinet et al, 2005), with positive associations being occasionally reported (Vinson, 1972;Lawrence et al, 1976). Rapid parasitoid development in 1st instar A. glycines shows that these hosts provide minimum required nutrient levels for B. communis (Henry et al, 2005) although parasitoids emerging from young hosts may be smaller. The gradual increase in development time on later A. glycines stages may reflect changes in nutritional value of the host, increased aphid resistance and competition of parasitoid larvae with the developing host embryos (Walker & Hoy, 2003;Colinet et al, 2005) or increased time necessary for development of a larger parasitoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both physiological and morphological changes in the host are related to development at a particular age, which varies and results in variation in its acceptability to the parasitoid and its suitability for the progeny of the parasitoid (Henry et al, 2005) Food quality is one of the most important factors, as pupae of different ages may not have the same nutritional quality. During the pupal development internal tissues undergo histolysis, histogenesis and differentiation to form adult internal organs and sclerotized appendages.…”
Section: Discussionmentioning
confidence: 99%
“…Geralmente, os parasitóides avaliam o tamanho como um indicador da qualidade do hospedeiro (Henry et al 2005), mas isso normalmente ocorre de forma mais clara com os parasitóides idiobiontes, os quais se desenvolvem em hospedeiros que não se alimentam durante o parasitismo (Li & Mills 2004). Entretanto essa característica pode não ser necessariamente verdadeira para os parasitóides cenobiontes, como L. testaceipes, cujas larvas se desenvolvem enquanto os hospedeiros ainda se alimentam e crescem (Sequeira & Mackauer 1994, Chau & Mackauer 2001.…”
unclassified